Grain Qualities, Oil Yields and Fatty Acid Composition of Some Hybrid Dent Corn Varieties - HULYA ORAK, H.; Z. KORKUT, KAYIHAN; BASER, ISMET; ORAK, ADNAN; BILGIN, OGUZ (Asian Journal of Chemistry, 2010)
In this study, the crude oil, protein, ash, potassium, sodium, ferrous content in corn grain and the characteristics of corn oil such as fatty acid composition, iodine value and specific gravity were determined of 35 hybrid dent corn varieties grown in Tekirdag ecological condition. The average grain yield was found betwwen 1099.32-796.32 kg/da in the corn varieties. The crude protein content in the analyzed varieties was ranged between 5.3 and 9.9 %. Among analyzed samples the oil content of corn varieties changed from 2.40 to 5.20 %. Variety G-626 had the higher saturated fatty acid (SFA), palmitic acid and oleic acid (MUFA) content from than the other varieties.